2016
DOI: 10.1007/978-3-319-38810-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Magnification of Cholesterol-Induced Membrane Resistance on the Tissue Level: Implications for Hypoxia

Abstract: High cellular membrane cholesterol is known to generate membrane resistance and reduce oxygen (O2) permeability. As such, cholesterol may contribute to the Warburg effect in tumor cells by stimulating intracellular hypoxia that cannot be detected from extracellular oxygen measurements. We probe the tissue- level impact of the phenomenon, asking whether layering of cells can magnify the influence of cholesterol, to modulate hypoxia in relation to capillary proximity. Using molecular dynamics simulations, we aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Subsequent investigations described this effect in detail, showing that the effect of cholesterol in lipid membrane structures is exceptionally prominent at the level of the cholesterol ring. , Unbiased molecular dynamics (MD) simulations showed that the rate of spontaneous water translocation through a membrane decreases by a factor of 7 when the content of cholesterol is increased from 0 to 33 mol % . This is in agreement with experimental studies that reported a 4-fold reduction of water permeability through a bilayer containing 25 mol % of cholesterol compared to a pure phospholipid bilayer. , Cholesterol has also been shown to decrease the membrane permeability to ions, small neutral molecules like glucose, , and gases such as oxygen. , Recent MD simulation studies have further shown that the free energy barrier of translocating certain drugs and nanoparticles across a lipid bilayer increases with increasing cholesterol content. In biological membranes, reduction of cholesterol concentration was observed to render them more permeable. , …”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Subsequent investigations described this effect in detail, showing that the effect of cholesterol in lipid membrane structures is exceptionally prominent at the level of the cholesterol ring. , Unbiased molecular dynamics (MD) simulations showed that the rate of spontaneous water translocation through a membrane decreases by a factor of 7 when the content of cholesterol is increased from 0 to 33 mol % . This is in agreement with experimental studies that reported a 4-fold reduction of water permeability through a bilayer containing 25 mol % of cholesterol compared to a pure phospholipid bilayer. , Cholesterol has also been shown to decrease the membrane permeability to ions, small neutral molecules like glucose, , and gases such as oxygen. , Recent MD simulation studies have further shown that the free energy barrier of translocating certain drugs and nanoparticles across a lipid bilayer increases with increasing cholesterol content. In biological membranes, reduction of cholesterol concentration was observed to render them more permeable. , …”
Section: Introductionsupporting
confidence: 58%
“… 1 , 8 10 Cholesterol has also been shown to decrease the membrane permeability to ions, 11 small neutral molecules like glucose, 12 , 13 and gases such as oxygen. 14 , 15 Recent MD simulation studies have further shown that the free energy barrier of translocating certain drugs and nanoparticles across a lipid bilayer increases with increasing cholesterol content. 16 18 In biological membranes, reduction of cholesterol concentration was observed to render them more permeable.…”
Section: Introductionmentioning
confidence: 99%
“…Force-field parameters for O 2 were developed in our laboratory. As described in Shea et al (45), the bond length was set to 1.21 Å , with a vibrational force constant of 849.16 kcal/mol$Å 2 and all other parameters defined the same as the Lipid 11 carbonyl oxygen (oC) atom type, which originated with the General Amber Force Field (GAFF) (46). O 2 molecules were introduced into the simulation systems by replacing water molecules to reach a concentration of 200 mM O 2 for the entire water-lipid system.…”
Section: Simulationsmentioning
confidence: 99%
“…This increased resistance should correspond with a permeability reduction of similar magnitude. While modest on a single-membrane level, the rate-reducing effect should be amplified as oxygen is required to cross or circumvent multiple membranes on its path toward mitochondria buried within tissues [18]. …”
Section: Discussionmentioning
confidence: 99%